A new generalized Weibull-Gompertz distribution and its properties. Issue 4 (19th May 2022) - Zendehdel, Javad; Zarei, Reza; Mahmoudi, Seyed Mahdi
Abstract: In this paper, we proposed a new lifetime distribution called new generalized Weibull-Gompertz (NGWG) by considering a serial system with one component following a Weibull distribution and another following a generalized Weibull-Gompertz distribution. Several properties of the NGWG such as hazard function, moments, order statistics and maximum likelihood and Bayesian estimation are studied in this paper. A real data set is analyzed and it is observed that the present distribution can provide a better fit than some other well-known distributions such as modified Weibull and beta modified Weibull.